Polymorphisms in CCL2&CCL5 chemokines/chemokine receptors genes and their association with diseases - Navratilova, Zdenka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2006)
BACKGROUND: Chemokines and chemokine receptors are major mediators of leukocyte trafficking into the sites of the immune response. They participate in defence against microbial infection, in Th1/Th2 polarization of the immune response, allograft rejection and angiogenesis/angiostasis as well as in tumorigenesis and metastasis. To date, several functional polymorphisms of chemokine and chemokine receptor genes have been discovered that are able to deregulate chemokine system and, therefore, they may interfere with the pathogenesis of a large number of inflammatory and other diseases. In this review we focus on the known polymorphisms of two chemokines: CCL2, CCL5 and their corresponding receptors (CCR2, CCR5) and we also discuss their associations with susceptibility and progression to selected immune-mediated diseases. METHODS AND RESULTS: Based on relevant literature this article gives a short overview of case-control and family studies regarding effect of the genetic factors on diseases such as coronary artery disease, systemic lupus erythematosus, diabetes mellitus, lung diseases and others. CONCLUSION: Recent advance in the identification of chemokine genetic background of the diseases could provide opportunity for pharmacological treatment. However, we need more information about posttranscriptional events to understand functional relevance of polymorphisms and to discovery new avenues to blocking disease development.
Keywords: Receptors, CCR2; receptory CCR2; lidé; chemokin CCL2; Chemokine CCL5; receptory CCR5; Polymorphism, Genetic; Receptors, CCR5; Chemokine CCL2; chemokin CCL5; polymorfismus genetický; Humans